1976
DOI: 10.1084/jem.144.1.167
|View full text |Cite
|
Sign up to set email alerts
|

Human B-lymphocyte antigens expressed by lymphocytic and myelocytic leukemia cells. I. Detection by rabbit antisera.

Abstract: A previously uncharacterized human B-lymphocyte antigen has been detected by rabbit antisera raised to papain digests of spleen cell membranes. The unabsorbed sera reacted in both cytotoxicity and immunofluorescent tests with normal B lymphocytes and cultured B-cell lines but not with normal T lymphocytes or cultured T-cell lines. The cytotoxicity titers against B cells were as high as 1:32,000, whereas the same sera undiluted were negative against T cells. By immunofluorescent staining 6-14% of unfractionated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0
1

Year Published

1977
1977
1982
1982

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(40 citation statements)
references
References 15 publications
0
39
0
1
Order By: Relevance
“…It has previously been reported that rabbit antisera prepared with papain digests of human malignant spleen cell membranes recognize antigens expressed by normal and neoplastic human B lymphocytes (1)(2)(3). The antigens recognized by these antisera appear to be similar to, and may be identical with, the p23, 30 antigen identified by Humphreys and colleagues and by Schlossman and colleagues on normal B cells, 15-20% of null cells, and the majority of acute leukemia cells (4,5).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…It has previously been reported that rabbit antisera prepared with papain digests of human malignant spleen cell membranes recognize antigens expressed by normal and neoplastic human B lymphocytes (1)(2)(3). The antigens recognized by these antisera appear to be similar to, and may be identical with, the p23, 30 antigen identified by Humphreys and colleagues and by Schlossman and colleagues on normal B cells, 15-20% of null cells, and the majority of acute leukemia cells (4,5).…”
mentioning
confidence: 73%
“…Permanent tissue culture lines of B cells (pooled lines B44, 45, and 47) and T cells (MOLT-4) were also used for absorption (1).…”
Section: Methodsmentioning
confidence: 99%
“…Later, they were detected by hetero-antisera raised against the isolated protein from cell membranes (2)(3)(4). In addition to their presence on B cells and monocytes, they have been detected on the leukemic blast in eases of acute lymphocytic leukemia, acute myelogenous leukemia, and chronic myelogenous leukemia in blastic crisis (4)(5)(6).…”
mentioning
confidence: 98%
“…Anti-Ta-like serum was obtained from Alpha Gamma Labs (Sierra Madre, California, U.S.A). The characteristics of the antiserum have been described in detail elsewhere (Billing et al, 1976 Sternberger et al (1970) as modified by Taylor (1974). The procedure has been described in detail by Papadimitriou et al (1978).…”
mentioning
confidence: 99%